Anmerkung zu EuGH, Urt. v. 4.6.2020 - C-301/18, Leonhard - Rodi, Daniel (GPR, 2020)
Article 7(4) of Directive 2002/65/EC of the European Parliament and of the Council of 23 September 2002 concerning the distance marketing of consumer financial services and amending Council Directive 90/619/EEC and Directives 97/7/EC and 98/27/EC must be interpreted as meaning that, where a consumer exercises his or her right to withdraw from a distance loan agreement concluded with a supplier, that consumer has the right to receive from that supplier, subject to certain sums which the consumer himself or herself is required to pay to the supplier under the conditions laid down in Article 7(1) and (3) of that directive, the principal repaid and the interest paid under that agreement, but does not have the right to receive compensation for the benefit of use of that principal and that interest.